Spanish rural landscapes: classification based on the spatial composition - García del Barrio, J. M.; Bolaños, F.; Elena-Rosselló, R. (Forest Systems, 2003)
This paper presents a new landscape taxonomy designed to classify the Spanish rural landscapes attending to the composition of their spatial elements. The matricidal, essential, marginal o residual presence of each land use/land cover type is used as the main taxonomical criteria. A sample of 412 rural landscapes (206 different landscapes analysed in two successive dates) fully representative of the biogeoclimatic diversity of Spain has been classified. About 39% of total rural landscapes tested were identified as forest landscapes, 22% as rangeland landscapes, 11% as agroforest landscapes and the remainder 28% as agricultural landscapes. To test the new taxonomy, a multivariate classification analysis has been carried out, defining the 12 commonest Spanish rural landscape types, being highly correlated to the established categories. After that test, it is concluded that the proposed taxonomy is preferable for its intuitively and interpretability, allowing to identify landscape types not present in the analysed sample.